2009
DOI: 10.3748/wjg.15.5827
|View full text |Cite
|
Sign up to set email alerts
|

Value of three-dimensional reconstructions in pancreaticcarcinoma using multidetector CT: Initial results

Abstract: AIM:To evaluate the use of three-dimensional imaging of pancreatic carcinoma using multidetector computed tomography (CT) in a prospective study. METHODS:Ten patients with suspected pancreatic tumors were examined prospectively using multidetector CT (Somatom Sensation 16, Siemens, Erlangen, Germany). The images were evaluated for the presence of a pancreatic carcinoma and invasion of the peripancreatic vessels and surrounding organs. Using the isotropic CT data sets, a three-dimensional image was created with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 19 publications
0
20
0
3
Order By: Relevance
“…Gemcitabine + erlotinib c, 8 Gemcitabine + capecitabine 9 Gemcitabine + cisplatin 10 (especially for patients with BRCA1/BRCA2 or other DNA repair mutations) Gemcitabine Capecitabine (category 2B) CI 5-FU (category 2B) Fixed-dose-rate gemcitabine, docetaxel, capecitabine (GTX regimen) 11 (category 2B) Fluoropyrimidine + oxaliplatin (category 2B) (eg, 5-FU/leucovorin/oxaliplatin 12 or CapeOx 13 ) Induction chemotherapy with any of the chemotherapy options above (≥4-6 cycles) followed by chemoradiation* ,d or SBRT 14 (in selected patients, locally advanced disease without systemic metastases) 15 Chemoradiation* ,e or SBRT e (in select patients who are not candidates for combination therapy)…”
Section: Panc-gmentioning
confidence: 99%
See 2 more Smart Citations
“…Gemcitabine + erlotinib c, 8 Gemcitabine + capecitabine 9 Gemcitabine + cisplatin 10 (especially for patients with BRCA1/BRCA2 or other DNA repair mutations) Gemcitabine Capecitabine (category 2B) CI 5-FU (category 2B) Fixed-dose-rate gemcitabine, docetaxel, capecitabine (GTX regimen) 11 (category 2B) Fluoropyrimidine + oxaliplatin (category 2B) (eg, 5-FU/leucovorin/oxaliplatin 12 or CapeOx 13 ) Induction chemotherapy with any of the chemotherapy options above (≥4-6 cycles) followed by chemoradiation* ,d or SBRT 14 (in selected patients, locally advanced disease without systemic metastases) 15 Chemoradiation* ,e or SBRT e (in select patients who are not candidates for combination therapy)…”
Section: Panc-gmentioning
confidence: 99%
“…Studies have shown that 70% to 85% of patients determined by CT imaging to have resectable tumors were able to undergo resection. 11,[13][14][15][16] Pancreas protocol MRI with contrast can be a helpful adjunct to CT in the staging of pancreatic cancer, particularly for characterization of CT-indeterminate liver lesions and when suspected tumors are not visible on CT or in cases of contrast allergy. 17,18 The difference in contrast enhancement between the parenchyma and adenocarcinoma is highest during the pancreatic phase, thereby providing a clear distinction between a hypodense lesion in the pancreas and the rest of the organ.…”
Section: Imaging Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A well-performed pancreatic protocol CT is a popular approach in staging pancreatic cancer and has been validated well in the literature. [13][14][15] MRI has also been proved equally efficacious in predicting vascular and nodal involvement. 16,17 CT, however, has limited capacity to characterize the nature of post-radiation soft tissue attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Опухоль обладает агрессив-ным ростом, выявляется на далеко зашедших стадиях, а пятилетняя выживаемость составля-ет всего 5%. Адъювантная химиотерапия явля-ется единственным способом, позволяющим увеличить выживаемость пациентов с R0 ре-зекцией [3,4].…”
Section: Diagnostic Value Of Three-dimensional Reconstructions Of Ct unclassified